Leibniz in the Eighteenth Century: Herder's Critical Reflections on the Principles of Nature and Grace - DeSouza, Nigel (British journal for the history of philosophy, 2012)
The subject of this article is Herder's unique conception of the soul-body relationship and its divergence from and dependence on Leibniz. Herder's theory is premised on a rejection of the windowlessness of monads in two important respects: interaction between material bodies (as gleaned from Crusius and Kant) and interaction between the soul and body. Herder's theory depends on Leibniz insofar as it agrees with the intimate connection Leibniz posits between the soul and the body, as his epistemology demonstrates, with, however, the significant modification that the connection is real. Herder transforms the Leibnizian rehabilitation and use of substantial forms to develop a double-conception of the human soul as both thinking substance and substantial form: the soul, qua thinking substance, needs a body through whose senses it can interact with, and acquire knowledge of, the external world; the soul, qua substantial form, constructs itself this material body by harnessing the forces of attraction and repulsion. Herder's theory provides an alternative to other contemporary accounts of the soul-body relationship, especially Kant's, which start from the problem of relating two distinct substances. His unique and original reconciliation of the modern dichotomy of spirit and matter, via his connecting of Leibniz's realms of final and efficient causes, is of great significance for the rise of German Idealism.